2009
DOI: 10.1111/j.1468-2850.2009.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Process transforms inputs to determine outcomes: Therapists are responsible for managing process.

Abstract: The variance in outcomes for psychotherapy patientsis not partitionable into components that are independent contributions of treatments, therapists, and patients. If these inputs did not influence one another over the course of psychotherapy, they could be independent and so have additive main-effects or interaction-effects on outcomes. But that is impossible because they do influence one another and therapists are responsible for actively managing the psychotherapy process by repeatedly adjusting these input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Our assessment of within-session practice elements was also limited to a focus on provider behavior, as opposed to more complex measurement of the interaction between therapist and client behavior. Given that psychotherapy is a dynamic, interactive endeavor, examining therapist behaviors alone provides just one perspective on therapeutic processes (Krause & Lutz, 2009). In an effort to complement this single perspective, we included youth and parent ratings of therapeutic alliance in the models, but only child alliance for only one outcome (i.e., inconsistent parenting) was associated with change.…”
Section: Discussionmentioning
confidence: 99%
“…Our assessment of within-session practice elements was also limited to a focus on provider behavior, as opposed to more complex measurement of the interaction between therapist and client behavior. Given that psychotherapy is a dynamic, interactive endeavor, examining therapist behaviors alone provides just one perspective on therapeutic processes (Krause & Lutz, 2009). In an effort to complement this single perspective, we included youth and parent ratings of therapeutic alliance in the models, but only child alliance for only one outcome (i.e., inconsistent parenting) was associated with change.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were marked differences in the process of therapy between participants, it was almost unanimous that it would be adapted when working within a time limit. Understanding the significance of these changes in process is, however, difficult in light of the ambiguity in what makes psychotherapy helpful (Dallos & Vetere, 2005), as well as in how process relates to outcome (Krause & Lutz, 2009; Stiles, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the study of principles and mechanisms of change is a promising avenue for research, it has been suggested that progress may be limited by the unsuitability of some quantitative methodologies to the study of the complex process of psychotherapy. Counter to the causal assumptions of the RCT methodology (Jadad & Enkin, ), several researchers have suggested that the process and outcomes of psychotherapy are causally entangled and influence one another (Budd & Hughes, ; Krause & Lutz, ). It has been noted that despite efforts to standardise the influence of various factors through treatment manualisation, clients and therapists find ways to vary their interactions to produce optimal outcomes (Budd & Hughes, ; Krause & Lutz, ).…”
Section: Limited Progress In Differentiating Treatment Effectivenessmentioning
confidence: 99%
“…Counter to the causal assumptions of the RCT methodology (Jadad & Enkin, ), several researchers have suggested that the process and outcomes of psychotherapy are causally entangled and influence one another (Budd & Hughes, ; Krause & Lutz, ). It has been noted that despite efforts to standardise the influence of various factors through treatment manualisation, clients and therapists find ways to vary their interactions to produce optimal outcomes (Budd & Hughes, ; Krause & Lutz, ). Additionally, the process of randomising participants to treatment conditions has minimised the importance of client's informed decision making about selecting treatments and therapists that suit them (Budd & Hughes, ; Stiles, Barkham, Connell, & Mellor‐Clark, ).…”
Section: Limited Progress In Differentiating Treatment Effectivenessmentioning
confidence: 99%